Financial Inclusion and Economic Empowerment - Khuan, Hendri (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the relationship between Financial Inclusion and Economic Empowerment, with a focus on the influence of access to formal financial services on individual economic independence and participation in economic decision making. Through systematic literature analysis, this study explores the concepts of Financial Inclusion and Economic Empowerment, as well as the factors that influence the relationship between the two. The research results show that increasing Financial Inclusion has the potential to increase Economic Empowerment, especially among marginalized groups and women. However, the success of implementing Financial Inclusion is influenced by various institutional, policy, technological, and social and cultural factors. This research highlights the importance of attention to inclusive policy frameworks and collaborative efforts between various stakeholders in achieving the goals of financial inclusion and sustainable economic empowerment.